Body as Capital: Construing Experiential Knowledge of Prostitution and Sex Slavery in Some Postcolonial African Literature - Kamalu, Ikenna (Journal of Gender and Power, 2019)
Previous studies on prostitution and sex slavery in African literature have focused chiefly on the thematic concerns of the novels such as the moral dimensions of the act but none of the studies has explored the role of language as a form of representation that enables the reader to infer the psychological conditions and attitudes of discourse participants either as victims of prostitution and sex slavery or as active agents in the sustenance of the act. Working within the systemic linguistic orientation and insights from the notion of phenomenalistic construal, therefore, this study explores the linguistic representation of the inner feelings and attitudes of victims of sex slavery and prostitution in Amma Darko’s Beyond the Horizon, Akachi Adimora-Ezeigbo’s Trafficked, and Ifeanyi Ajaegbo’s Sarah House. The texts under study represent sex slavery and prostitution as forms of physical and mental violence against the victims of the acts and a gross violation of their humanness.